Hepatitis B Virus Evasion From Cyclic Guanosine Monophosphate–Adenosine Monophosphate Synthase Sensing in Human Hepatocytes. Issue 5 (10th July 2018) - Verrier, Eloi R.; Yim, Seung‐Ae; Heydmann, Laura; El Saghire, Houssein; Bach, Charlotte; Turon‐Lagot, Vincent; Mailly, Laurent; Durand, Sarah C.; Lucifora, Julie; Durantel, David; Pessaux, Patrick; Manel, Nicolas; et al.
Abstract : Chronic hepatitis B virus (HBV) infection is a major cause of chronic liver disease and cancer worldwide. The mechanisms of viral genome sensing and the evasion of innate immune responses by HBV infection are still poorly understood. Recently, the cyclic guanosine monophosphate–adenosine monophosphate synthase (cGAS) was identified as a DNA sensor. In this study, we investigated the functional role of cGAS in sensing HBV infection and elucidate the mechanisms of viral evasion. We performed functional studies including loss‐of‐function and gain‐of‐function experiments combined with cGAS effector gene expression profiling in an infectious cell culture model, primary human hepatocytes, and HBV‐infected human liver chimeric mice. Here, we show that cGAS is expressed in the human liver, primary human hepatocytes, and human liver chimeric mice. While naked relaxed‐circular HBV DNA is sensed in a cGAS‐dependent manner in hepatoma cell lines and primary human hepatocytes, host cell recognition of viral nucleic acids is abolished during HBV infection, suggesting escape from sensing, likely during packaging of the genome into the viral capsid. While the hepatocyte cGAS pathway is functionally active, as shown by reduction of viral covalently closed circular DNA levels in gain‐of‐function studies, HBV infection suppressed cGAS expression and function in cell culture models and humanized mice. Conclusion : HBV exploits multiple strategies to evade sensing and antiviral activity of cGAS and its effector pathways.